Farmer's young adult children their socio-economic roles and life aspirations. - Fajanilan, Ma. Lucilyn E. (2016.)
This study identify socio-economic roles, participation in work, and life aspirations of farmer's young adult children. They did household chores and practiced being good students. Traditional gender roles surfaced as females performed more household chores than males and more males were involved in farming activities than females. There was low participation in faming activities, whether involved in farming or not, majority of the respondents had no desires to continue farming or to enter the industry. Their aspirations centered on achieving educational attainment and to have financial success in the future. They also hope to help their family and later on their commjunity after achieving their goals.g
Special Problem -- Bachelor of Arts, Psychology. University of the Philippines Visayas, Iloilo.
Keywords: Socio-Economic.; Participation; Aspiration